Does Sharia Impurity Affect Sharia Banking Performance - Sulhani; Mughni, Abdul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
This research aims to analyze the factors that cause the insignificant development of sharia banking performance in Indonesia. This research focuses on identifying practices that are not purely sharia as the causal factors that hinder the development of sharia banking. The population in this research is Sharia Commercial Banks (BUS) registered with the Financial Services Authority (OJK) in the 2014-2018 period. The data obtained was analyzed using multiple regression with panel data. The results of this research indicate that murabahah financing and profits from transactions denominated in foreign currency have a negative effect on the performance of sharia banking. Financing murabaha proven to increase Non-Performing Financing (NPF), in addition, transactions denominated in foreign currency are proven to reduce Return on Assets (ROA), as well as increase Operating Expenses, Operating Income (BOPO) and NPF of sharia banking. Meanwhile, non-halal income has no effect on sharia banking performance. The implication of this research is that sharia banking must improve operational practices that are not purely sharia to make them pure sharia. The two regulators, namely the OJK and the government, create a more conducive environment so that sharia banking is able to implement operational practices in accordance with sharia principles.